Group Cohesiveness On Performance: Mediating Effect Of Collective Organization Citizenship Behavior - Ikhsan Maksum; T. Hani Handoko; Nur Laili Fikriah (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
Organizational Citizenship Behavior towards Organizations (OCBO) concerning the organization's benefits in general and Organizational Citizenship Behavior towards Individuals (OCBI) concerning specific benefits obtained by individuals in the organization and contributes to the organization. The research aims to examine the role of mediating the collective organizational citizenship behavior on the influence of group cohesiveness on group performance based on social exchange theory and social identity theory. The object of research is working groups on the creative industries in Yogyakarta. The study used field settings and cross-sectional study designs. Research respondents were 39 working groups consisting of 300 group members and using the regression analysis technique as a research hypothesis testing technique. The results showed that collective organizational citizenship behavior (OCBO and OCBI) partially mediated the effect of group cohesiveness on group performance.